2023
DOI: 10.1590/s2179-975x3722
|View full text |Cite
|
Sign up to set email alerts
|

Ornamental aquaculture as a pathway for the introduction of non-native fish in coastal drainage of northeastern Brazil

Jefferson Saulo da Vitória Luduvice,
Marcelo Fulgêncio Guedes Brito

Abstract: Aim We present the first record of the introduction of three non-native ornamental fish species, resulting from ornamental aquaculture escapes on the Northeast Mata Atlântica hydrographic ecoregion, with information on the reproductive activity. Methods The specimens were collected bimonthly between 2018 and 2019 using seine and sieve nets, and analyzed for determination of reproductive phases. Results A total of 830 specimens were collected, corresponding to the species Hyphessobrycon eques (N= 311), Poecil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…We also recorded a higher frequency of females. A similar pattern was found for feral P. reticulata and X. maculatus introduced into a stream located in Sergipe State and in Australia Luduvice & Brito, 2023). The prevalence of females may also be associated with high predation pressure, which may cause differential predation risk between females and males.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We also recorded a higher frequency of females. A similar pattern was found for feral P. reticulata and X. maculatus introduced into a stream located in Sergipe State and in Australia Luduvice & Brito, 2023). The prevalence of females may also be associated with high predation pressure, which may cause differential predation risk between females and males.…”
Section: Discussionsupporting
confidence: 70%
“…This is probably the lowest size found in introduced populations of feral P. reticulata and X. maculatus. In other sites and environments throughout Brazil and the world, the smallest reproductive size of feral guppy and southern platyfish ranged between 1.2-2.0 cm, and 1.7-2.0 cm SL respectively Andrade et al, 2008;Montag et al, 2011;Kırankaya & Ekmekçi, 2021;Luduvice & Brito, 2023). In the present study, we also found smallest females of P. reticulata and X. maculatus measuring 4.4-5.0 cm TL respectively, indicating a feralization process for both species.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation